2013
DOI: 10.3390/polym5031081
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Solution Properties of Double Hydrophilic Poly(ethylene oxide)-block-poly(2-ethyl-2-oxazoline) (PEO-b-PEtOx) Star Block Copolymers

Abstract: Abstract:We demonstrate the synthesis of star-shaped poly(ethylene oxide)-block-poly(2-ethyl-2-oxazoline) [PEO m -b-PEtOx n ] x block copolymers with eight arms using two different approaches, either the "arm-first" or the "core-first" strategy. Different lengths of the outer PEtOx blocks ranging from 16 to 75 repeating units were used, and the obtained materials [PEO 28 -b-PEtOx x ] 8 were characterized via size exclusion chromatography (SEC), nuclear magnetic resonance spectroscopy (NMR), and Fourier-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Aggregates with hydrodynamic radii of 104 nm were observed for PEO 107 ‐ b ‐PMeOx 64 and 270 nm for PEO 107 ‐ b ‐PMeOx 112 , respectively. Schacher and co‐workers observed aggregation of PEO‐ b ‐poly(2‐ethyl‐2‐oxazoline) (PEO‐ b ‐PEtOx) eight‐arm star polymers in aqueous solution . Turbid solutions were obtained that contained polymer particles with hydrodynamic radii of several hundred nm even at concentrations below 0.5 g L −1 .…”
Section: Double Hydrophilic Block Copolymer Systems For Self‐assemblymentioning
confidence: 99%
“…Aggregates with hydrodynamic radii of 104 nm were observed for PEO 107 ‐ b ‐PMeOx 64 and 270 nm for PEO 107 ‐ b ‐PMeOx 112 , respectively. Schacher and co‐workers observed aggregation of PEO‐ b ‐poly(2‐ethyl‐2‐oxazoline) (PEO‐ b ‐PEtOx) eight‐arm star polymers in aqueous solution . Turbid solutions were obtained that contained polymer particles with hydrodynamic radii of several hundred nm even at concentrations below 0.5 g L −1 .…”
Section: Double Hydrophilic Block Copolymer Systems For Self‐assemblymentioning
confidence: 99%
“…Furthermore, Rudolph et al showed that MALDI, static light scattering (SLS) and 2D-LC are essential to obtain absolute molar masses, and to confirm the architecture of their star-shaped [PEO -b-PEtOx] , which was synthesized by the coppercatalyzed azide-alkyne cycloaddition reaction (CuAAC). These techniques are necessary considering that NMR spectroscopy and SEC are not satisfactory to fully characterize these systems [126].…”
Section: Star-shaped Polymersmentioning
confidence: 99%
“…48 In a similar approach, star polymers have been prepared starting from azido-functionalized β-cyclodextrin. 33 However, conjugation of hydrophilic PAOx (PMeOx or PEtOx) with hydrophobic polymer blocks offers even more possibilities towards complex architectures due to microphase segregation of immiscible polymer segments.…”
Section: Applications Of Chain-end Clickable Poly(2-oxazoline)smentioning
confidence: 99%